ENSURING THE GUARANTEED LEVEL OF FLIGHTS SAFETY – THE VIEW OF THE FUTURE - Kharchenko, Volodymyr; Alexeiev, Oleh; Kolesnyk, Tamara (Proceedings of National Aviation University, 2019)
Considering statistics for the last decade on accident/incident of a question of providing guaranteed flight safety level is the most relevant as shortcomings and problems of functioning aviation activity are explained by lack of general-theoretical basis and the standard scientifically based approaches to safety management system which development has to be guided upon the demand of ICAO which defines that any region should not have accident/incident frequency level more than twice exceeds universal. These are the following main areas: introduction of an acceptable level of flight safety in the state; mandatory procedures for the development and implementation of safety management system; obligatory procedures for ensuring direct management of the level of the flight safety within acceptable or established level of the enterprise (continuous monitoring and regular assessment of the flight safety, corrective actions required to maintain the agreed flight safety indicators and monitoring, flight information analysis, risk management, etc.) [1,2]. Purpose of methodology consists in association in the only complex of tasks of assessment, providing and verification of safety aviation activities as complex hierarchical structure with independent critical elements and also hardware, program, network and ergatic komponen which are both means, and subject to safety. The realization of ensuring the guaranteed result consists in realization of management processes so that not to allow transition of infrastructure or its systems to potentially dangerous state and to provide blocking (exception) of the corresponding technical object in case of threat of transition or upon transition to a dangerous state and minimization of consequences of such transition.